CAPTURE OF IMPLEMENTATION GOLD TAX IN INDONESIA FACT: HOW IS THE EFFECT FOR GOVERNMENT REVENUE AND INVESTOR GOLD BEHAVIOR - Mulyono, Resha Dwi Ayu Pangesti; Aziz, Nur Kholik; Fakhrurrozi, Muhammad Dhito (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Gold taxation in Indonesia has experienced regulatory dynamics in recent years. These regulatory changes aim to manage state revenue and govern public behavior in investment. This study seeks to analyze the impact of gold tax implementation on state revenue and investor behavior patterns, such as Income Tax Article 22 of 0.25% on gold trading transactions and Value-Added Tax (VAT) ranging from 1.1% to 1.65% on gold jewelry. The research method employed is qualitative descriptive using secondary data and an empirical analysis approach. Secondary data sources include tax regulations, state revenue reports, global and domestic gold price trends, as well as international gold demand reports. The findings indicate that gold taxation can increase state revenue through improved payment compliance due to simplified regulations and moderate rates, while still being influenced by market mechanisms, gold price cycles, and purchasing power. From the perspective of investor behavior, the tax policy tends not to significantly reduce investment interest, though it does put some pressure on short-term investors. Ultimately, investor behavior continues to position gold as a long-term hedging asset.